Measurement of Image Distance Using Only Camera On Object Detection OpenCV - F. Friendly; Harizahayu Harizahayu; Rahmat Widya Sembiring; Berti Sari Br Sembiring (INFOKUM, 2021)
Image processing combine with machine learning is used widely in image recognition, image classification, and image detection. By using camera to detect an object has been done within several article. The other usage of image and object detection is in measurement of distance. Distance measurement is possible by using additional peripheral such as sensor and extra camera. This research is intended to elaborate the usage of single camera in detecting and measuring distance. The distance set between the camera and the object. In this research, author used a square object with different size and different distance range. By using one of the known data as a pivot in calculating other image distance, the average error between 4%-7% . These result was achieved by using different object size. The bigger the size of the object used as reference, the smaller the error percentage of the measurement.